2012
DOI: 10.1007/s00425-012-1808-6
|View full text |Cite
|
Sign up to set email alerts
|

The plant Selaginella moellendorffii possesses enzymes for synthesis and hydrolysis of the compatible solutes mannosylglycerate and glucosylglycerate

Abstract: A mannosylglycerate synthase (MgS) gene detected in the genome of Selaginella moellendorffii was expressed in E. coli and the recombinant enzyme was purified and characterized. A remarkable and unprecedented feature of this enzyme was the ability to efficiently synthesize mannosylglycerate (MG) and glucosylglycerate (GG) alike, with maximal activity at 50 °C, pH 8.0 and with Mg(2+) as reaction enhancer. We have also identified a novel glycoside hydrolase gene in this plant's genome, which was functionally conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Genes coding for proteins with significant amino acid identity to MgH could be detected in mycobacterial genomes but, unlike the GG biosynthetic genes identified in all the available genomes, mgH homologues were, with a few exceptions, almost exclusively detected in RGM (Table 1). The characterization of the M. hassiacum enzyme confirmed that, unlike the MgHs from the thermophilic bacteria Thermus thermophilus and Rubrobacter radiotolerans or the eukaryotic MgH from Selaginella moellendorffii that hydrolyze MG and GG alike, GG was by far the preferred substrate of the M. hassiacum enzyme, for which we propose the designation GG hydrolase (GgH)2425.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Genes coding for proteins with significant amino acid identity to MgH could be detected in mycobacterial genomes but, unlike the GG biosynthetic genes identified in all the available genomes, mgH homologues were, with a few exceptions, almost exclusively detected in RGM (Table 1). The characterization of the M. hassiacum enzyme confirmed that, unlike the MgHs from the thermophilic bacteria Thermus thermophilus and Rubrobacter radiotolerans or the eukaryotic MgH from Selaginella moellendorffii that hydrolyze MG and GG alike, GG was by far the preferred substrate of the M. hassiacum enzyme, for which we propose the designation GG hydrolase (GgH)2425.…”
Section: Discussionmentioning
confidence: 75%
“…Recently, a glycosyl hydrolase able to hydrolyze mannosylglycerate (MG), a GG-related osmolyte common in hyperthermophilic archaea and some thermophilic bacteria, was identified in Thermus thermophilus and designated mannosylglycerate hydrolase (MgH)24. Despite the fact that this organism only accumulates MG and not GG, MgH was also shown to efficiently hydrolyze GG, as were the functional MgHs detected in Rubrobacter radiotolerans and in the primitive plant Selaginella moellendorffii 25.…”
mentioning
confidence: 99%
“…Until now, no experimental evidence for the occurrence of GGA in α‐proteobacteria was found. It has been found in cyano‐ and γ‐proteobacteria and in the archaeon Methanohalophilus portucalensis , the aquificae Persephonella marina and, recently, in the plant Selaginella moellendorffii (Robertson et al ., ; Cánovas et al ., ; Goude et al ., ; Costa et al ., ; Empadinhas and da Costa, ; Nobre et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…Recently, the genes coding for GGA and MGA synthesis enzymes were characterised in the primitive land plant Selaginella moellendorffii (Nobre et al . ). The authors’ provided evidence that the genes for these enzymes were probably acquired via horizontal gene transfer from MGA‐accumulating bacteria.…”
Section: Related Compounds – Sugar‐glycerate Compoundsmentioning
confidence: 97%
“…Related genes were also detected in many other genomes of red algae and other eukaryotes, including green algae and fungi, from which no MGA or GGA accumulation has ever been reported (Borges et al 2014). Recently, the genes coding for GGA and MGA synthesis enzymes were characterised in the primitive land plant Selaginella moellendorffii (Nobre et al 2013). The authors' provided evidence that the genes for these enzymes were probably acquired via horizontal gene transfer from MGA-accumulating bacteria.…”
Section: Related Compounds -Sugar-glycerate Compoundsmentioning
confidence: 98%